A Comprehensive Review On The Use Of Vascularized Fibular Graft For The Reconstruction Of Long Defect: The USM experience - Yusof, Mohd Imran (2000)
Skeletal defects following trauma or bone tumor resection may be successfully treated by conventional bone grafting or bone transport. however for massive defect following en bloc resection of a localized tumor, chronic osteomyelitis or following trauma, the reconstruction of such defects in really challenging. vascularized fibular graft is one of the treatment alternative since 1975 when Taylor first reported the successful use of the graft for the reconstruction of a tibial defect. in malaysia, vascularized fibular grafting for the management of massive bone loss is still new. Currently, this procedure has not been widely performed in Malaysia. In USM, A total number of 19 vascularized fibular graft had been performed involving the reconstruction of limbs within a period of 29 months.